Role of dentin cross-linking agents in optimizing dentin bond durability. (October 2017) - Abunawareg, M.; Abuelenain, D.A.; Elkassas, D.; Haimed, T. Abu; Al-Dharrab, A.; Zidan, A.; Hassan, A.H.; Pashley, D.
Abstract: The present work compared the effects of 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide hydrochloride (EDC-HCl) and ultraviolet (UV)- or blue light-activated riboflavin cross-linking agents on resin–dentin micro-tensile bond strength and nanoleakage in bonds produced using a two-step, etch-and-rinse adhesive after three storage intervals (24 h, 6 months, and 12 months). Forty eight extracted human third molars were used to investigate micro-tensile bond strength and interfacial nanoleakage in resin–dentin bonds created using Adper Single Bond 2, with or without pretreatment of acid-etched dentin surfaces. Either 0.5 M EDC-HCl or 1% riboflavin-5-phosphate activated by blue or UV light were used as cross-linking agents. Samples were evaluated after storage for 24 h, 6 months, or 12 months in distilled water at 37 °C. Statistical analyses revealed that 12 months of storage resulted in significant decreases in the bond strength of the controls (p < 0.003), with significant increases in their silver nanoleakage (p < 0.05), compared with the groups subjected to dentin pretreatment with either EDC-HCl or light-activated 1% riboflavin. Despite the significant drop in bond strength after 6 months' storage in all experimental groups compared with the 24-h bond strength (p < 0.05), there was a further non-significant drop in bond strength after 12 months in samples treated with EDC-HCl and UV-activated 1% riboflavin (p > 0.05). Dental collagen cross-linking induced by UV- or blue light-activated 1% riboflavin or EDC-HCl enhanced the durability and strength of the resin–dentin bond.